Regulatory T Cell Heterogeneity in the Thymus: Impact on Their Functional Activities - Santamaria, Jérémy C.; Borelli, Alexia; Irla, Magali (Frontiers in Immunology, 2021)
Foxp3+ regulatory T cells (Treg) maintain the integrity of the organism by preventing excessive immune responses. These cells protect against autoimmune diseases but are also important regulators of other immune responses including inflammation, allergy, infection and tumors. Furthermore, they exert non-immune functions such as tissue repair and regeneration. In the periphery, Foxp3+ Treg have emerged as a highly heterogeneous cell population with distinct molecular and functional properties. Foxp3+ Treg mainly develop within the thymus where they receive instructive signals for their differentiation. Recent studies have revealed that thymic Treg are also heterogeneous with two distinct precursors that give rise to mature Foxp3+ Treg exhibiting non-overlapping regulatory activities characterized by a differential ability to control different types of autoimmune reactions. Furthermore, the thymic Treg cell pool is not only composed of newly developing Treg, but also contain a large fraction of recirculating peripheral cells. Here, we review the two pathways of thymic Treg cell differentiation and their potential impact on Treg activity in the periphery. We also summarize our current knowledge on recirculating peripheral Treg in the thymus.